Recent developments in applied electrostatics : proceedings of the Fifth International Conference on Applied Electrostatics, November 2-5, 2004, Shanghai, China - Sun, Keping; Yu, Gefei; International Conference on Applied Electrostatics (5th : 2004 : Shanghai) (Kidlington, Oxford : Elsevier, 2004)
40